What is P(A' n B') if P(A)=0.4, P(B)=0.3 and P(A n B)=0.15

Watch
blueynuey
Badges: 5
Rep:
?
#1
Report Thread starter 3 years ago
#1
P(A)=0.4
P(B)=0.3
P(A n B)=0.15

Find P(A' n B').

I wanted to confirm if the answer is 0.55 or 0.45, and tell me which method you used to solve this thank you.
0
reply
yusyus
Badges: 21
Rep:
?
#2
Report 3 years ago
#2
(Original post by blueynuey)
P(A)=0.4
P(B)=0.3
P(A n B)=0.15

Find P(A' n B'.

I wanted to confirm if the answer is 0.55 or 0.45, and tell me which method you used to solve this thank you.
try drawing a Venn diagram of A and B, their intersection will be 0.15, you want to find the probability outside of both circles
1
reply
shanks21
Badges: 2
Rep:
?
#3
Report 3 years ago
#3
answer: P(A' n B';) = 0.45

[finding the probability of just A] P(A n B';) = P(B) - P(A n B) = 0.4 - 0.15 = 0.25

[finding [the probability of just B] P(B n A';) = P(B) - P(A n B) = 0.3 - 0.15 = 0.15

therefore [probability of A or B] P(A u B) = P(A n B';) + P(A n B) + P(B n A';) = 0.25 + 0.15 + 0.15 = 0.55

finally P(A' n B';) = 1 - P(A u B) = 1 - 0.55 = 0.45
0
reply
username3579622
Badges: 1
Rep:
?
#4
Report 3 years ago
#4
Assuming your P is a probability space:

P(A n B) = P(A) + P(B) - P(A u B)

Then using De Morgan's Law

P(A' n B') = P(A') + P(B') - P(A' u B')
= P(A') + P(B') - P( (A n B)')
= P(A') + P(B') - ( 1 - P( A n B) )
= ( 1 - P(A) ) ( 1 - P(B) ) - ( 1 - P( A n B) )
0
reply
Shaanv
Badges: 17
Rep:
?
#5
Report 3 years ago
#5
P(A' n B') is the probability that what is not in A intersects with what is not in B. If u draw the venn diagram the answer will become clear.
1
reply
ghostwalker
  • Study Helper
Badges: 17
#6
Report 3 years ago
#6
(Original post by blueynuey)
P(A)=0.4
P(B)=0.3
P(A n B)=0.15

Find P(A' n B'.

I wanted to confirm if the answer is 0.55 or 0.45, and tell me which method you used to solve this thank you.
I'd use:

P(AuB)= P(A)+P(B)-P(AnB)

and

P(A' n B') = P( (AuB)' ) = 1- P(AuB)
1
reply
vasanti.sai
Badges: 1
Rep:
?
#7
Report 7 months ago
#7
give formulas correctly...P(A n B' = P(B) - P(A n B)this is a big blunder....in place of P(B) there should beP(A)
0
reply
DFranklin
Badges: 18
Rep:
?
#8
Report 7 months ago
#8
(Original post by vasanti.sai)
give formulas correctly...P(A n B' = P(B) - P(A n B)this is a big blunder....in place of P(B) there should beP(A)
Typing B instead of A is a slip-up.

Replying to a post made 3 years ago.... priceless.
0
reply
X

Quick Reply

Attached files
Write a reply...
Reply
new posts
Back
to top
Latest
My Feed

See more of what you like on
The Student Room

You can personalise what you see on TSR. Tell us a little about yourself to get started.

Personalise

Do you think mandatory Relationships and Sex Education in secondary schools is a good idea?

Yes (358)
84.04%
No (68)
15.96%

Watched Threads

View All